2010
DOI: 10.1038/jid.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Human Eccrine Sweat Gland Cells Can Reconstitute a Stratified Epidermis

Abstract: Eccrine sweat glands are generally considered to be a possible epidermal stem cell source. Here we compared the multilayered epithelia formed by epidermal keratinocytes and those formed by eccrine sweat gland cells. We demonstrated both in vitro and in vivo the capability of human eccrine sweat gland cells to form a stratified interfollicular epidermis substitute on collagen hydrogels. This is substantiated by the following findings: (1) a stratified epidermis consisting of 10-12 cell layers is formed by sweat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 51 publications
7
117
0
1
Order By: Relevance
“…The ability of sweat glands to regenerate the straight duct was supported by the observation that the residues of human sweat glands following dermal trauma regenerated the dermal duct of sweat glands (Lobitz et al, 1956). Furthermore, Biedermann et al (2010) suggested that human sweat glands contain multipotent cells. They demonstrated that cells derived from microsurgically isolated sweat gland organs were capable of reconstituting a multilayered epidermis-like structure in vitro (Biedermann et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The ability of sweat glands to regenerate the straight duct was supported by the observation that the residues of human sweat glands following dermal trauma regenerated the dermal duct of sweat glands (Lobitz et al, 1956). Furthermore, Biedermann et al (2010) suggested that human sweat glands contain multipotent cells. They demonstrated that cells derived from microsurgically isolated sweat gland organs were capable of reconstituting a multilayered epidermis-like structure in vitro (Biedermann et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, Biedermann et al (2010) suggested that human sweat glands contain multipotent cells. They demonstrated that cells derived from microsurgically isolated sweat gland organs were capable of reconstituting a multilayered epidermis-like structure in vitro (Biedermann et al, 2010). Although these studies suggested that sweat glands contain multipotent cells, it remains elusive which compartments of sweat glands contribute to the regeneration of the ductal portion and possess self-renewal ability.…”
Section: Discussionmentioning
confidence: 99%
“…O wilgotności skóry decyduje liczba i aktywność wydzielnicza gruczołów potowych, szczególnie ekrynowych, których produkt to elektrolit, składający się niemal wyłącznie z wody. Im wyższa aktywność gruczołowa, tym wyższe stężenie elektrolitów, większe przewodnictwo elektryczne tkanki i mniejsza bioimpedancja [5,6,7,8].…”
Section: Dyskusjaunclassified
“…Due to the abundance of sweat glands in relation to hair follicles in the majority of human skin areas, it has been hypothesized that another source of progenitors and/or stem cells within the sweat apparatus (duct and gland) can contribute to the skin wound repair [69][70][71].…”
Section: Sweat Glands Stem Cellsmentioning
confidence: 99%